Selected poems - Dickinson, Emily, 1830-1886.; Moore, Jackie, 1940- (New York : Oxford University Press, 2006)
A collection of more than fifty poems by Emily Dickinson that includes introductory essays, notes on her work and life, discussion of themes, language, issues, and critical history, further reading suggestions, and other student resources.
Includes bibliographical references (p. 194-195).
Young Adult
Keywords: Dickinson, Emily, -- 1830-1886 -- Criticism and interpretation; Dickinson, Emily, -- 1830-1886 -- Criticism